Investigation of Protein Export in Bifidobacterium breve UCC2003 - MacConaill, Laura E. (American Society for Microbiology, 2003)
The molecular interactions between the bifidobacterial cell and its natural environment, namely, the gastrointestinal tract of its host, are particularly important in understanding the presumed positive effects of Bifidobacterium on the health status of the host. In this study an export-specific reporter system, designed for use in gram-positive organisms and based on the use of the staphylococcal nuclease (Nuc) as a reporter, was employed to identify exported proteins in Bifidobacterium breve UCC2003. A B. breve genomic library of translational fusions to the Nuc-encoding gene devoid of its own export signal was established in the shuttle vector pFUN (I. Poquet, S. D. Ehrlich, and A. Gruss, J. Bacteriol. 180:1904-1912, 1998) and screened for bifidobacterial export signals. Sequence analysis of the fusion proteins obtained that displayed a nuclease-producing phenotype in both Lactococcus lactis and B. breve predicted the presence of a classical signal peptide and/or single or multiple transmembrane domains, thus indicating that some of the export signals in B. breve are comparable to those used in L. lactis. Cell fractionation studies, zymograms, nuclease assays, and Western blotting were employed to confirm the function of the predicted signals and to determine the location and activity of the exported fusion proteins in B. breve and/or L. lactis.